The Visual Paradigm in Qur’ān Memorization: A Study of Color-Block Effectiveness in the General Community - Satria Kharimul Qolbi; Muhammad Sayiful Nurasman; Hazma; Waway Qodratulloh Suhendar (Studia Quranika, 2026)
This study investigates the effectiveness of the color-block method in Qur'ān memorization from the perspective of the general community, focusing on sustaining long-term retention and reducing forgetfulness among memorizers of diverse ages, professions, and educational backgrounds. A descriptive quantitative design was employed, involving 17 purposively selected participants. Data were collected through participant observation, semi-structured interviews, and a Likert-scale questionnaire, then analyzed using SPSS. The findings indicate high acceptance of the color-block method, with item means ranging from 3.94 to 4.47 (aggregate mean = 29.41/35, SD = 4.258). Respondents reported improvements in ease of recall, memorization speed, page differentiation, and concentration, suggesting that color functions as an effective visual cue supporting cognitive processing during tahfīẓ. However, benefits related to spatial recall of verse position were less consistent, reflecting individual differences in learning strategies and spatial memory. Participants also demonstrated strong willingness to adopt and recommend the method, indicating favorable conditions for broader implementation in community-based tahfīẓ settings. The study concludes that the One Day One Color (ODOC) approach represents a practical and innovative learning aid with implications for mentor training, palette standardization, and curriculum development. Future experimental and longitudinal studies are recommended to validate these descriptive findings using objective measures of memorization performance.